Praksisnær viden og refleksion over religion og dannelse - Kirsten M. Andersen; Lakshmi Sigurdsson (Tidsskrift for Professionsstudier, 2019)
The article considers how the teacher’s practice in the school subject Religious Education can be included in teacher education with a double purpose 1) scaffolding the preparation of the student’s internship and 2) qualifying the didactic dialogue among the students by insight into the results from an action research project and thus integrate practice-oriented knowledge in the vocational studies at a university college. We suggest a framework for a pedagogical reflection of teaching practice in RE, which is defined as educating towards religious competence.